Occupational Hazard and Risk Assessment for Confined Space Rescue Operation at Cement Manufacturing Industries - Naimuddin, Nurul Sakinah; Syahrun Niezam Mohd Dzulkifli,; Amira Zulkarnain,; Mohd Hilmi Mohamed Zainal Abidin, (Progress in Engineering Application and Technology, 2024)
Hazard identification during rescue in confined spaces is crucial to promptly recognize and mitigate evolving risks, ensuring the safety of both rescuers and individuals in distress, especially in dynamic environments where conditions can change rapidly. The objective of this study is to identify hazards connected to the rescue operation of a preheater cyclone for a person who has collapsed while working in the cement manufacturing industry. A preheater cyclone in cement manufacturing is typically considered as a confined space. There are a number of methods that have been pursued in order to acquire the information that is required to accomplish the objective. Several techniques were used to complete the hazard identification such as conducting field observation, interview with expert, hazard identification checklist, document review and literature review. Upon completion of the assessment, a comprehensive total of 27 hazards were identified, encompassing a spectrum of categories including physical, chemical, biological, ergonomic, and psychosocial hazards. A total of 27 hazards were identified, with 24 falling under the category of safety-related hazards, and the remaining three categorized as health-related hazards. Specifically, within the identified hazards, 24 were ascribed to physical hazards, two were attributed to chemical hazards, one was associated with biological hazards, while ergonomic and physiological hazards each accounted for one hazard. This comprehensive classification underscores the diverse nature of the identified risks, necessitating targeted strategies for mitigation across multiple hazard categories.